Hubungan Partus Lama dengan Terjadinya Perdarahan Post Partum Primer di RSU Pemangkat Periode Januari s.d. Desember 2015 - Therecia Wijayati (LPPM STIKES Al-Ma'arif Baturaja, 2020)
As data obtained from the Indonesian Ministry of Health (2008) shows that the Maternal Mortality Rate (MMR) in Indonesia reaches 290.8 per 100,000 live births. This means that more than 1,800 mothers die per year or 2 mothers die every hour or as a result of abortion and complications in pregnancy, bleeding and eclampsia in childbirth, and postpartum infections. Research Methods: In this study, the research design used was a case control study with a retrospective approach. This study aims to see the risk of bleeding due to prolonged labor. Results: It shows that the highest number of incidents of prolonged labor was ≤ 24 hours, as many as 35 cases (51.5%), while primary post partum hemorrhage was 34 (50%). Labor that lasts more than 24 hours is called prolonged labor. Prolonged labor always poses a risk / complication for either the mother or the fetus she is carrying. Conclusion: The results showed that most of the respondents who experienced primary post partum hemorrhage were with labor> 24 hours, as many as 24 (36.8%) cases. The results of the analysis showed that there was a relationship between prolonged labor and the incidence of primary post partum hemorrhage with a value of P = 0.000 and the estimated incidence of primary partum hemorrhage in prolonged labor was calculated with OR = 9.03 times.